APPLE APP STORE PLATFORMFOR DIGITAL PUBLISHING IN LITHUANIA - ŽARKOVA, ALISA (Knygotyra, 2013)
The aim of this article is to determine how effectively the Lithuanian publishers exploit new emerging publishing possibilities to expand the market to the whole world – the Apple App Store platform. In order to achieve this goal, the following objectives have been identified: defining the digital book distribution platform concept; comparing digital book platform distribution in publishing approach; finding out the main digital book distribution methods and comparing them; examining a range of Lithuanian digital books in the Apple App Store platform; investigating readers’ demand for digital books in the Apple App Store platform. After analyzing scientific literature and other information sources, through comparative and generalization method the concept of the platform has been formed. Furthermore, the article deals with the comparison of digital book platform distribution in publishing approach and clarification of the major digital book publication methods. Part of the study using a structured interview questionnaire and descriptive statistical methods is aimed at analyzing the Lithuanian digital book of fers in the Apples App Store platforms and research of digital book readers’ needs in the Apple App Store platform.In summarizing the results, it can be concluded that Apple App Store platform is still little exploited by Lithuanian publishers, but judging by an increasingly growing distribution in different titles of digital books every year, it is possible to predict that the situation will change in the near future.The results reveal that market-related issues also allow to predict the future prospects of the market segments, which may be useful for publishing professionals and self-publishers. This bachelor work may be useful to publishers, distributors of digital books, multifunction equipment suppliers and manufacturers, digital book readers as well as both researchers and students of the Faculties in Communication and Information Studies.
Keywords: ...